Anatomical Parameters for Occipital Condyle Screws: An Analysis of 500 Condyles Using CT Scans. Issue 7 (September 2022) - Bernstein, David N.; Ikpeze, Tochukwu C.; Foxx, Kenneth; Omar, Adan; Mesfin, Addisu
Study Design: Retrospective observational study. Objective: To establish occipital condyle dimensions (length, width, height), as well as the medialization angle necessary for safe occipital condyle screw placement in occipitocervical fixation. Methods: Between 1/2014-6/2014, patients who presented to a single level 1 academic trauma center emergency room and received computed tomography (CT) imaging of the cervical spine as part of routine clinical care were identified. After excluding patients with cervical fractures, neoplastic disease, or infection, 500 condyles representing 250 patients were analyzed. Condyle length, height, and width (all reported in millimeters [mm]) were evaluated on the sagittal, coronal, and axial series, respectively. Medialization angle (reported in degrees) was evaluated on the axial series of CT imaging. Measurements were compared by sex and age. Results: The average condyle length, width, and height were 18.6 millimeters (mm) (range, 14.5-23.0 mm), 10.5 mm (range, 7.4-13.8 mm), and 11.3 mm (7.1-15.3 mm), respectively. Additionally, the average occipital condyle medialization angle was 23° (range, 14-32°). Occipital condyles of men were significantly longer, wider, and taller (all comparisons, p < 0.05). The medialization angle was significantly steeper for women than men (p < 0.05). No measurement differences were appreciated by age. Conclusion: Our findings are similar to previous studies in the field; however, length appears slightly shorter. Further, measurement differences were appreciated by sex but not age. Thus, our measurement findings emphasize the importance of preoperative planning utilizing individual patient anatomy to ensure safe placement of occipital condyle screws for optimal outcomes.